The lost jackals from the Brazilian caves: insights on the taxonomy and paleoecology of Pleistocene bush dog Speothos pacivorus (Carnivora, Canidae) - Ruiz, Juan V. [UNESP]; Ferreira, Gabriel S.; Machado, Fabio A.; Kyriakouli, Christina; Godoy, Pedro L.; Gundlach, Carsten; Castro, Mariela C.; Montefeltro, Felipe C. [UNESP] (Taylor & Francis, 2025)
Speothos pacivorus from the Pleistocene of Brazilian Intertropical Region (BIR) is distinguished from the extant bush dog S. venaticus by its larger size and key characters of the skeleton and teeth. Nonetheless, its taxonomic status is volatile, with some authors still considering both species as synonymous. Here, we aimed to summarize morphofunctional differences between S. pacivorus and S. venaticus through a comparative description of their skull and dentition, geometric morphometric analysis (GMM), and finite element analysis (FEA). Our GMM revealed S. pacivorus significantly separated from the sampled specimens of S. venaticus, and a regression analysis showed that the morphological differences of its cranium are not size-related, reinforcing its status as a separate species. Both exhibited very akin von Mises’ stress average and distribution on FEA’s results, suggesting similar prey-capturing strategies. Our results bolster the hypothesis that the coexistence of these hypercarnivorous canids in the BIR could be explained by a diverse megaherbivore community, allowing resource partitioning between different canid species. Following the demise of these megaherbivores in the Pleistocene–Holocene boundary, other large hypercarnivorous canids also became extinct, leaving the small S. venaticus, able to subsist on smaller prey, as the sole surviving species of this specialized lineage.